STUDI FENOMENOLOGI: KEPEMIMPINAN GEN Y DI PERUM BULOG KANWIL BALI - Setyaningrum, Ariani; Surya Perdana, Mirwan (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to understand how Generation X, Y, and Z perceive Generation Y leadership at Perum Bulog Kanwil Bali. Using a qualitative phenomenological approach, the research explores the experiences and perspectives of different generations regarding Gen Y leadership in a dynamic work environment. The main focus of this study is: (i) how Gen Y leaders develop effective leadership styles and (ii) how Generation X, Y, and Z assess their leadership in addressing organizational challenges and achieving performance targets.The respondents in this study consisted of representatives from Generation X, Y, and Z at Perum Bulog Kanwil Bali, selected through purposive sampling. Data collection was conducted through in-depth interviews and direct observations to gain a comprehensive understanding of each generation's perception of Gen Y leadership.The findings indicate that Generation X tends to perceive Gen Y leadership as more flexible and innovative but still faces challenges in adapting to a more hierarchical work system. Meanwhile, Generation Y views their peers' leadership style as collaborative, technology-driven, and prioritizing work-life balance. On the other hand, Generation Z sees Gen Y leadership as inspiring and open to change but expects more structured communication and guidance. Overall, this study confirms that Gen Y leadership at Perum Bulog Kanwil Bali emphasizes openness, innovation, and a mentoring and coaching approach, despite facing bureaucratic challenges and differing generational expectations within the organization.